Efflux pumps as potential targets for biofilm inhibition - Ren, Jingyi; Wang, Meijuan; Zhou, Wenjuan; Liu, Zhonghao (Frontiers in Microbiology, 2024)
Biofilms account for a great deal of infectious diseases and contribute significantly to antimicrobial resistance. Efflux pumps confer antimicrobial resistance to microorganisms and involve multiple processes of biofilm formation. Efflux pump inhibitors (EPIs) are attracting considerable attention as a biofilm inhibition strategy. The regulatory functions of efflux pumps in biofilm formation such as mediating adherence, quorum sensing (QS) systems, and the expression of biofilm-associated genes have been increasingly identified. The versatile properties confer efflux pumps both positive and negative effects on biofilm formation. Furthermore, the expression and function of efflux pumps in biofilm formation are species-specific. Therefore, this review aims to detail the double-edged sword role of efflux pumps in biofilm formation to provide potential inhibition targets and give an overview of the effects of EPIs on biofilm formation.